Angola : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1997)
This paper provides an analysis of important factors that have affected the Angolan economy in recent years. The paper summarizes political developments since 1992 and provides an overview of developments in each major sector of the economy. The paper surveys the trade regime and reform priorities affecting it, summarizes available information on poverty, and describes issues affecting development of the diamond sector, formerly a mainstay of the Angolan economy. The paper also provides a technical analysis of the authorities' current monetary rule, and a summary of the tax system.